Ophthalmic ropinirole is an equally effective emetic agent in healthy dogs compared to intravenous apomorphine - Lee, Jack A.; Como, Katie; Zhu, Xiaojuan; Schildt, Julie (Frontiers in Veterinary Science, 2025)
IntroductionEmesis is commonly induced in the veterinary setting due to toxin or foreign material ingestion. The dopamine agonist apomorphine is commonly used for this indication. The novel dopamine-2 specific agonist ropinirole was approved by the U.S. Food and Drug Administration for this indication in 2020. Data to compare the efficacy and adverse effects profile of these medications is important for clinical decision making.MethodsThis blinded randomized crossover trial compared the efficacy of intravenous apomorphine to ophthalmic ropinirole in 24 healthy dogs. Factors assessed include efficacy at inducing vomiting within 20 min, need for redosing of the emetic agent, time to start of emesis, and incidence of adverse effects.ResultsBoth apomorphine and ropinirole were highly effective at emesis induction, with 95.8 and 100% success rates, respectively, and no difference between groups. Repeated dosing was needed after 20 min in 25% of the apomorphine group and 8.3% of the ropinirole group for successful emesis induction. Median time to onset was significantly shorter with apomorphine (1.18 min) than ropinirole (8.85 min). Incidence of adverse effects was similar, with a higher incidence of ocular redness and protracted vomiting in the ropinirole group.ConclusionThese results suggest similar efficacy of ropinirole compared to apomorphine, with similar adverse effect rates.